MODERNISASI PENDIDIKAN: POTRET DINAMIKA SOSIAL PENDIDIKAN PESANTREN DALAM NOVEL NEGERI 5 MENARA KARYA AHMAD FUADI - Naeli Wardani; Heru S.P. Saputra; Sunarti Mustamar (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2020)
This research discusses the pesantren (Islamic boarding school) education system's reflection in the novel entitled Negeri 5 Menara. The research method used is qualitative in the sociology of literature approach. It is used to cover up the author's social context, literature as a reflection of society, and literature's social function. The study results in the author's social context show that author creativity is motivated by the author's experience and social construction of the author's ideology. In literature as a reflection of society, it described some similarities are found between Pondok Madani and Pondok Modern Darussalam Gontor (PMDG) in implementing a modern education system. It shows that the novel is a representation of social conditions. Modernity in the education system at the pesantren includes jasus [spy], the strict of time discipline, discipline in dress, mudhaharah (speech in three languages), memorization of Arabic vocabulary, use of foreign languages (Arabic and English), a system of admission with selection, and extracurricular activities. In the social function of literature, there are several responses from readers in assessing the novel Negeri 5 Menara's benefits. The author's contribution in giving a message to readers is focused on the function of socio-educationalism.